A survey in practicing supply chain management of Hong Kong industries. (26th August 2008) - Chan, Felix T.S.; Chan, H.K.
Supply Chain Management (SCM) and advanced Information Technology (IT) are crucial management tools that have changed the way how business can gain competitive advantages. By linking these two elements, this paper presents a study on the impacts of different facets of SCM on Hong Kong industries. Critical success factors in practicing SCM for individual industries were identified based on their time devoted on the supply chain issues, and ranking of the supply chain activities. The results of this study can be regarded as a reference on some focus supply chain areas to the companies of similar industries.